2003
DOI: 10.1128/aem.69.9.5290-5296.2003
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Acidic pH on Expression of Surface-Associated Proteins of Streptococcus oralis

Abstract: Streptococcus oralis, a member of the mitis group of oral streptococci, is implicated in the pathogenesis of infective endocarditis and is the predominant aciduric non-mutans-group streptococcus in dental plaque. We undertook to identify the most abundant surface-associated proteins of S. oralis and to investigate changes in protein expression when the organism was grown under acidic culture conditions. Surface-associated proteins were extracted from cells grown in batch culture, separated by two-dimensional g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
72
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(76 citation statements)
references
References 39 publications
3
72
0
1
Order By: Relevance
“…Glycolytic enzymes were considered, because of their highly conserved nature, to be related simply to substrate turnover (27) bronectin, which assist the bacteria in generating an inflammatory response (28,29). Streptococcus oralis, a member of the oral biofilm but also associated with extraoral diseases, including endocarditis and bacteremia in neutropenic patients, also has enolase and glyceraldehyde-3-phosphate dehydrogenase at its cell surface as well as two other glycolytic enzymes, phosphoglycerate kinase and fructose bisphosphate aldolase (42). The expression of these enzymes was enhanced in the biofilm cells and if these are also surface associated in S. mutans they could be involved in the adhesion process.…”
Section: Resultsmentioning
confidence: 99%
“…Glycolytic enzymes were considered, because of their highly conserved nature, to be related simply to substrate turnover (27) bronectin, which assist the bacteria in generating an inflammatory response (28,29). Streptococcus oralis, a member of the oral biofilm but also associated with extraoral diseases, including endocarditis and bacteremia in neutropenic patients, also has enolase and glyceraldehyde-3-phosphate dehydrogenase at its cell surface as well as two other glycolytic enzymes, phosphoglycerate kinase and fructose bisphosphate aldolase (42). The expression of these enzymes was enhanced in the biofilm cells and if these are also surface associated in S. mutans they could be involved in the adhesion process.…”
Section: Resultsmentioning
confidence: 99%
“…However, 21 of the 66 identified RV-reduced/disappearing protein spots (Table II), such as ␀-1,4-xylanase, pollen allergens, ␀-expansin, polygalacturonase, profilin A, enolase, and ascorbate peroxidase, have been detected in coat/wall-associated and pollen-released protein fractions of mature rice (14) and maize pollen (20). Further analyses revealed that 1) most of the identified RVreduced/disappearing proteins, such as members of the class III peroxidase family, polygalacturonase, and disulfide isomerase, have a potential extracellular targeting signal peptide in their N termini (Table II), and 2) 24 have been documented to be secreted/released extracellular proteins and/or cell surface/wall-associated proteins in other organisms, for example 2,3-bisphosphoglycerate-independent phosphoglycerate mutase (26), fructose-1,6-bisphosphate aldolase (27), and triose-phosphate isomerase (28). Thus, we propose that 51 of the 66 RV-reduced/disappearing identities (39 Unipros) were probably released, and the other 15 (14 Unipros) may really be down-regulated (Table II).…”
Section: And E)mentioning
confidence: 99%
“…How is lysis timing achieved if the endolysin is already secreted across the cytoplasmic membrane? Confounding the resolution of these issues is the limited understanding of the nature of the murein envelope in Gram-positive bacteria, where little is known about the chemical environment, and where, unexpectedly, high levels of a wide range cytosolic enzymes have been found (5).…”
mentioning
confidence: 99%